Reviewing effectivity in security approaches towards strengthening internet architecture - Vidya M. S.; Mala C. Patil (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The usage of existing Internet architecture is shrouded by various security loopholes and hence is highly ineffective towards resisting potential threats over internet. Hence, it is claimed that future internet architecture has been evolved as a solution to address this security gaps of existing internet architecture. Therefore, this paper initiates its discussion by reviewing the existing practices of web security in conventional internet architecture and has also discussed about some recent solutions towards mitigating potentially reported threats e.g. cross-site scripting, SQL inject, and distributed denial-of-service. The paper has also discussed some of the recent research contribution towards security solution considering future internet architecture. The proposed manuscripts contributes to showcase the true effectiveness of existing approaches with respect to advantages and limitation of existing approaches along with explicit highlights of existing research problems that requires immediate attention.